2002
DOI: 10.1016/s0550-3213(02)00561-8
|View full text |Cite
|
Sign up to set email alerts
|

The B+−Bd0 lifetime difference beyond leading logarithms

Abstract: We compute perturbative QCD corrections to the lifetime splitting between the charged and neutral B meson in the framework of the heavy quark expansion. These next-to-leading logarithmic corrections are necessary for a meaningful use of hadronic matrix elements of local operators from lattice gauge theory. We find the uncertainties associated with the choices of renormalization scale and scheme significantly reduced compared to the leading-order result. We include the full dependence on the charm-quark mass m … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
174
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(190 citation statements)
references
References 24 publications
10
174
1
1
Order By: Relevance
“…This feature has been studied in refs. [10,28]. The NLO result for ∆Γ JHEP10(2017)191 expressed throughz is numerically very well reproduced ifz is set to zero in the NLO correction.…”
Section: Jhep10(2017)191mentioning
confidence: 77%
See 1 more Smart Citation
“…This feature has been studied in refs. [10,28]. The NLO result for ∆Γ JHEP10(2017)191 expressed throughz is numerically very well reproduced ifz is set to zero in the NLO correction.…”
Section: Jhep10(2017)191mentioning
confidence: 77%
“…(18) of ref. [28]. Since we have set z = 0 in the charm lines attached to weak vertices, no NNLO corrections to the transformation occur.…”
Section: Phenomenology Of ∆γmentioning
confidence: 99%
“…The result in [9] was the first complete calculation of perturbative QCD effects beyond the leading logarithmic approximation to spectator effects in the HQE for heavy hadron decays. Currently NLO-QCD corrections to spectator effects are known for the lifetime ratios of heavy hadrons [18,19,20] and for ∆Γ B d and the semileptonic CP-asymmetries [21,10].…”
Section: Introductionmentioning
confidence: 99%
“…In these papers the full expressions for G s,xy and G s,xy S are given; they also include contributions from the QCD penguin operators Q 1 -Q 6 and the chromo-magnetic penguin operator Q 8 . (Beneke et al, 2002) found that the use ofm c (m b ) (charm mass at the bottom mass scale) instead ofm c (m c ), sums up large logs of the form m 2 c /m 2 b ln m 2 c /m 2 b to all orders; we will thus use the parameterz in our numerical analysis, given byz …”
mentioning
confidence: 99%